Tokyo ESP. 2 - Segawa, Hajime (Vertical, Inc, 2015)
"The professor appears. Schools of flying, glowing fish, a flying penguin, now a flying hippo? As Murasaki wrestles with how to effectively use her newfound powers, Rinka and Kyotaro continue to train with the wise (and wicked) Youdani, who introduces a boy with a unique type of precognition, which is put to the test when he has to make a difficult decision when a conservative family member is threatened by supernatural powers. The enigmatic Professor, the ringleader of delinquent superhumans, appears with a tantalizing piece of the ESP puzzle and an invitation to the other side..."- cover